Judicial Roles in Nonjudicial Functions - Nuno Garoupa; Tom Ginsburg (Washington University Global Studies Law Review, 2013)
Judges perform nonjudicial functions in many contexts. Most jurisdictions regulate these functions in multiple ways, by statute and by custom. We provide a theory of judicial demand and judicial supply for nonjudicial functions. By teasing out the determinants of judicial involvement in nonjudicial functions, we show the potential market failures and the need for regulation. We suggest that some limitations on the judicial exercise of nonjudicial functions seem justified. However, these limits might vary across jurisdictions depending on institutional and contextual factors.
Keywords: judges; judicial roles; judicial function; judicial demand; judicial supply